Analysis of Zakat Literacy in Kudus Regency, Central Java Province: A Mixed-Method Approach - Azzah, Farah Nailal; Santosa, Purbayu Budi (ZISWAF, 2022)
Assessing zakat literacy is needed for zakat institutions to examine zakat collection policies and evaluate zakat education and socialization programs. This study aims to map the level of zakat literacy in the Kudus Regency using the Zakat Literacy Index and unearth the factors which influence people's behavior in paying zakat. This study uses a mixed method with a sequential explanatory design. The results showed that the level of zakat literacy in the Kudus Regency was in the moderate category, with a Zakat Literacy Index score of 77.39. This study also shows that trust in scholars, peer influence, and education factors have influenced people's behavior and zakat understanding level. This paper also proffers implications to optimize the role of the zakat collector unit in order to increase the zakat knowledge of the community and the urgency of innovative and sustainable distribution programs.